Using social bookmarking to enhance critical thinking in higher education - Špiranec, Sonja (Array, 2011)
Web 2.0 and its abundant and ever increasing number of services represent a shifting pedagogical paradigm. Although discussions regarding the use of Web 2.0 services in the educational domain are rather optimistic, it is important to incorporate these services and tools in meaningful ways by taking pedagogical considerations and educational frameworks as a point of departure instead of attractiveness and popularity. A core aim and key learning outcome that has defined university education from its beginning is critical thinking. The first part of the paper focuses on the correlation between critical thinking and one of the Web 2.0 services, namely social bookmarking. This correspondence is based on theoretical frameworks which suggest that learners are involved in the discovery of knowledge and are constantly interacting with complex information environments. It is exactly during the process of connecting, interacting, evaluating and utilizing information that learning processes happen, but only if the interaction happens in a meaningful way and the student critically questions and interprets information. In the second part of the paper, the authors present how they use social bookmarking systems in their teaching. Within the courses, students are not only actively participating in the provision of content but also annotate, organize and index (or tag) it, which creates an effective framework for fostering critical thinking.